Proposing a Wiki-Based Technique for Collaborative Essay Writing - Mabel Ortiz Navarrete; Anita Ferreira Cabrera (Profile: Issues in Teachers' Professional Development)
This paper aims at proposing a technique for students learning English as a foreign language when they collaboratively write an argumentative essay in a wiki environment. A wiki environment and collaborative work play an important role within the academic writing task. Nevertheless, an appropriate and systematic work assignment is required in order to make use of both. In this paper the proposed technique when writing a collaborative essay mainly attempts to provide the most effective way to enhance equal participation among group members by taking as a base computer mediated collaboration. Within this context, the students’ role is clearly defined and individual and collaborative tasks are explained.